Entrepreneurial knowledge and digital entrepreneurial intention mediated by entrepreneurial alertness among Indonesian polytechnic students - Purwandari, Suci; Sadik, Safiah (International Journal Labs, 2024)
Advances in digital technology and the impact of the Covid-19 pandemic have resulted in significant growth in digital entrepreneurship in Indonesia. Apart from contributing to a country's economic development, digital entrepreneurship also has the potential to overcome youth unemployment. However, student participation rates remain low, possibly due to a lack of entrepreneurial knowledge. Furthermore, differences in entrepreneurship education approaches offered by universities result in differences in entrepreneurial knowledge among students. This research aims to analyze the factors that influence digital entrepreneurship intentions among polytechnic students in Indonesia. The survey was conducted with a sample of 268 polytechnic students throughout Central Java, using purposive and proportional random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This research finds the influence of entrepreneurial knowledge on digital entrepreneurial intentions and entrepreneurial alertness. Entrepreneurial alertness influences the relationship between entrepreneurial knowledge and digital entrepreneurial intention. These findings can inform strategies to foster digital entrepreneurship among Indonesian polytechnic students by focusing on increasing entrepreneurial knowledge and entrepreneurship alertness to accelerate the growth of digital entrepreneurship among the younger generation.